Penggunaan Media Audio Visual Dalam Meningkatkan Hasil Belajar IPA Siswa Kelas V Parepare - Khadafi, Muhammad; Syamsuardi, Syamsuardi; Ingriyani, Ingriyani (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2025)
AbstractAbstractThis research is a classroom action research that aims to find out how the use of audio visual media to improve students' science learning outcomes. The formulation of the problem in this research is whether the use of audio visual media can improve science learning outcomes for fifth grade students at UPTD SD Negeri 80 Parepare. The data collection instrument used documentation, tests and observations. Data analysis techniques in this study are reducing data, describing data and drawing conclusions. Based on the results of the research in the first cycle, the teacher did not provide guidance to students so that they did not dare to express their opinion. The results of the observation of the first cycle of the first meeting and the second meeting found that 9 out of 16 students got a complete score (56.25%) and 7 people out of 16 students (43.75%)) who got an incomplete score so that based on the completeness obtained it was still are in the sufficient category. Meanwhile, in cycle II, students have the courage to express their opinions and ask questions that are still not understood in relation to the material. In the second cycle of the first and second meetings, it was found that 13 out of 16 students (81.25%) got a complete score and 3 out of 16 students (18.75%) who got an incomplete score in the good category indicating the learning objectives were achieved by Thus, the use of Audio Visual media can improve students' science learning outcomes. Keywords: Audio Visual Media, Learning Outcomes, Science Penelitian ini adalah penelitian tindakan kelas yang bertujuan untuk mengetahui bagaimana penggunaan media Audio visual untuk meningkatkan hasil belajar IPA siswa. Adapun rumusan masalah dalam penelitian ini yaitu apakah penggunaan media audio visul dapat meningkatkan hasil belajar IPA Siswa kelas V UPTD SD Negeri 80 Parepare. Instrumen pengumpulan data menggunakan dokumentasi, tes dan observasi. Teknik analisis data dalam penelitian ini yaitu mereduksi data, mendeskripsikan data dan penarikan kesimpulan. Berdasarkan hasil penelitian pada siklus I guru kurang memberikan bimbingan kepada siswa sehingga belum berani mengemukakakn pendapatnya . Hasil observasi tindakan siklus I pertemuan pertaman dan pertemuan kedua ditemukan bahwa 9 orang dari 16 siswa memperoleh nilai tuntas (56,25 %) dan 7 orang dari 16 siswa (43,75 %)) yang memperoleh nilai tidak tuntas sehingga berdasarkan ketuntasan yang diperoleh masih berada pada kategori cukup. Sedangkan pada siklus II siswa sudah berani menemukakan pendapatnya dan menanyakan hal-hal yang masih kurang dipahami sehubungan dengan materi. Pada siklus II pertemuan pertama dan kedua ditemukan bahwa 13 orang dari 16 siswa (81,25 %) yang memperoleh nilai tuntas dan 3 orang dari 16 siswa (18,75 %) yang memperoleh nilai tidak tuntas dalam kategori baik yang menunjukkan tujuan pembelajaran tercapai dengan demikian, penggunaan media Audio Visual dapat meningkatkan hasil belajar IPA siswa. Kata kunci: Media Audio Visual, Hasil Belajar, IPA